THRIFTED BY STEV BUSINESS MODEL DEVELOPMENT - Iwan Suhardjo; Stefhanie Stefhanie (Universitas Internasional Batam, 2023)
During the fourth digital revolution, more people prefer online shopping. Therefore, the competition between online shops are very strong. A business is established with the aim of generating profit. In order to make a large amount of profit, the process requires skills, development of brand’s identity and good stakeholders inside the business. Common problem that faced by a lot of MSMEs (Micro, Small and Medium Enterprises) especially online based is the lack of skills and knowledge to make the business survive and cope through the trends that is forming on social media. Thrifted By Stev is a MSMEs based in Batam that is selling across social media as a medium for selling preloved bags founded in 2019 by Stefhanie. Thrifted By Stev is currently facing the common problem and needs to make a breakthrough. By joining the class from Young Entreprenur Academy, Thrifted by Stev can make a breakthrough and survives the digital revolution and expand its online based business.